2016
DOI: 10.1093/bja/aew119
|View full text |Cite
|
Sign up to set email alerts
|

Immediate postoperative extubation in bilateral lung transplantation: predictive factors and outcomes

Abstract: Our protocol allowed for extubation of 46% of bilateral lung transplant patients without increased postoperative risks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…However, little information was provided regarding predictive factors of success or long-term follow-up. Our team showed that OR extubation was possible in nearly half of cystic fibrosis 10 and COPD/emphysema patients, 11 with few cases of reintubation. Interestingly, in both types of patients, OR extubation was associated with a simpler postoperative course with a low rate of reintubation, a lower prevalence of PGD3 and a shorter ICU length of stay than ICU extubation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, little information was provided regarding predictive factors of success or long-term follow-up. Our team showed that OR extubation was possible in nearly half of cystic fibrosis 10 and COPD/emphysema patients, 11 with few cases of reintubation. Interestingly, in both types of patients, OR extubation was associated with a simpler postoperative course with a low rate of reintubation, a lower prevalence of PGD3 and a shorter ICU length of stay than ICU extubation.…”
Section: Discussionmentioning
confidence: 99%
“…However, our team has routinely adopted an OR extubation strategy according to the following fundamental practices: the use of short-acting drugs combined with effective analgesia, such as thoracic epidural analgesia; the avoidance of excessive fluid support; the maintenance of normothermia; and the application of systematic postoperative noninvasive ventilation. 9 Our group published an OR extubation strategy based on data from two separate cohorts considering specific populations: cystic fibrosis patients 10 and emphysema or chronic obstructive pulmonary disease (COPD) patients. 11 The main objective of the present study was to predict the prognosis of patients extubated immediately by comparing it with the prognosis of patients extubated in the ICU.…”
Section: Introductionmentioning
confidence: 99%
“…30 Despite the call for randomized trials by Myles et al., no study on ultrafast-track or immediate extubation after lung transplantation has been published. 31 Two cohorts have been reported more recently: one of CF patients by Felten et al in 2016 32 and one of COPD patients by Assenzo et al in 2018. 33 Both studies reported the feasibility of immediate extubation "in the operating room" in approximately half of the patients, and pulmonary graft dysfunction and one-year mortality were relatively better in COPD patients.…”
Section: Discussionmentioning
confidence: 99%
“…15,22 In hemodynamically stable patients with Pao 2 /Fio 2 greater than 300 mmHg, early extubation in the operating room has been described as feasible. 23 In patients with a high risk of severe primary graft dysfunction 5 or inadequate gas exchange, sedation and mechanical ventilation are usually intentionally weaned in a slower fashion (over 3 to 5 days). When weaning from mechanical ventilation becomes challenging and is prolonged to longer than 1 week, early tracheostomy is considered.…”
Section: Review Articlementioning
confidence: 99%